Demand, public procurement and transformation - Jakob Edler (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2023)
In this article we want to explore the role of the state to influence and support the demand for innovation in the context of transformation with a triple focus. First, we discuss the importance of demand for innovation and transformation. Second, we elaborate the conceptual underpinning of state intervention on the demand side. This In doing so, we link the demand side interventions with both the transformation debate and the innovation based competitiveness of systems debate. We then zoom into the main focus of this discussion paper, public demand and public procurement practice for innovation and transformation as this is - or can be - a powerful lever to spur both transformation and innovation which is largely underexplored and underused. Here we differentiate different forms of public procurement as well as different functions it can play in different transformation contexts. Rather than elaborating individual instruments and measures to support procurement, which is done in many ways elsewhere, we conclude with a number of high level recommendation for policy and analysis in order to further a debate the value of which has been recognised, but yet which has not materialised in any serious policy strategies for procurement.
Keywords: 330; Demand-side policies; State intervention; Public procurement; Sectoral policies; Transformation and innovation